2018
DOI: 10.1016/j.nicl.2018.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV Infection, methamphetamine dependence and age on cortical thickness, area and volume

Abstract: ObjectiveThis study examined the effects of HIV infection, methamphetamine dependence and their interaction on cortical thickness, area and volume, as well as the potential interactive effects on cortical morphometry of HIV and methamphetamine with age.MethodT1-weighted structural images were obtained on a 3.0T General Electric MR750 scanner. Freesurfer v5.3.0 was used to derive cortical thickness, area and volume measures in thirty-four regions based on Desikan-Killiany atlas labels.ResultsFollowing correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…In addition, decreased glutamate + glutamine was observed in the precuneus in early abstinent MADs 83 . Cortical thickness trended smaller in precuneus in MADs 84 . Consequently, we speculate that the decreased ReHo in the left precuneus is related to dysregulation of the exteroception process due to MA use.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, decreased glutamate + glutamine was observed in the precuneus in early abstinent MADs 83 . Cortical thickness trended smaller in precuneus in MADs 84 . Consequently, we speculate that the decreased ReHo in the left precuneus is related to dysregulation of the exteroception process due to MA use.…”
Section: Discussionmentioning
confidence: 89%
“…Structural magnetic resonance imaging (sMRI) could be quantified by plenty of brain structural metrics such as volume and cortical thickness (CTH), which have been widely used in HIV diseases (Correa et al, 2016; MacDuffie et al, 2018; Sanford et al, 2017; Sanford, Ances, et al, 2018). For example, gray matter volumetric alternations in putamen and caudate were observed in earliest HIV‐infected state (Kallianpur et al, 2020) and in primary HIV infection durations (Ragin et al, 2012), and played a key role in the multimodal classification for HIV patients (Sui et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such procedures are then followed by a multiple testing correction leading to an increased number of false negatives and, consequently, to reduced power. For instance, after multiple testing correction was applied in MacDuffie et al (2018), there were no brain regions found with cortical thickness significantly related to the HIV diagnosis, although smaller global cortical area and volume were observed in HIV‐positive participants with lower nadir CD4 count.…”
Section: Discussionmentioning
confidence: 99%
“…All considered approaches discovered regions located mostly in left parietal and frontal brain lobes. The cortical thickness of these brain regions is often reported as being significantly reduced by HIV infection (MacDuffie et al, 2018; Sanford et al, 2018). In particular, changes in mean cortical thickness in the left precentral and the supramarginal gyrus were found to be significantly associated with HIV infection Kallianpur et al (2012), while significantly lower cortical thickness in the bilateral postcentral region in HIV patients was observed by Yadav et al (2017).…”
Section: Discussionmentioning
confidence: 99%